Evaluation of selected physical and mechanical properties of multiple leader Acacia crassicarpa A. Cunn. Ex. Benth. genotypes - Ab Shukor, Nor Aini; Md. Tahir, Paridah; Jaafar, Mohd Faisal; Muhammad Roseley, Adlin Sabrina (Universiti Putra Malaysia Press, 2013)
A study on the evaluation of the selected physical and mechanical properties of multiple leadered Acacia crassicarpa A. Cunn. Ex. Benth, genotype was carried out to maximize its utilization. The study involved two classes of multiple leaders (ML), namely; ML2 (two leadered stems) and ML3 more than two leadered stems and 4 provenances: Claudie River, and Chillie Beach from Queensland (QLD) and Bensbach WP and Bimadebum WP from Papua New Guinea (PNG). ML classes showed significant difference at P<0.05 for physical properties but not between provenances. ML2 produced better mean values of specific gravity, radial and tangential shrinkage, with the values of 0.48%, 1.4% and 2.89% respectively compared to ML3 with values of 0.45, 3.56%, and 5.83%, respectively. Similarly, the ML classes were found to be significantly different at P<0.05 for Modulus of Elasticity (MOE) and Modulus of Rupture (MOR). Once again, ML2 produced higher mean values of 9858.4 N/mm2 and 89.63 N/mm2 for MOE and MOR, respectively, than ML3 (7557.7 N/mm2 and 60.4 N/mm2 respectively). Based on the physical and mechanical properties, it can be concluded that ML2 is more superior in terms of strength and stiffness than ML3.